Book ReviewsThe New Science of Management Decision, SimonHerbert A. rev. ed. (Englewood Cliffs, N.J.: Prentice-Hall, 1977), 175 pp., hardback $10.95, paper $5.95 - Hershauer, James C. (Academy of Management Review, 1978)
The article reviews the book ?The New Science of Management Decision,? by Herbert A. Simon.